Dengue Vector Control in Malaysia- Challenges and Recent Advances - HL, Lee; A, Rohani; MS, Khadri; WA, Nazni; H, Rozilawati; AH, Nurulhusna; AH, Nor Afizah; A, Roziah; R, Rosilawati; CH, Teh (IIUM Medical Journal Malaysia, 2015)
Dengue is a serious mosquito borne disease common in tropical and sub-tropical countries including Malaysia. There is at present a lack of specific treatment and an effective tetravalent vaccine against dengue. The control of dengue depends solely on the suppression of the two most important vectors namely, Aedes aegypti and Ae albopictus. Despite intensive and extensive control efforts by health agencies, the disease continues to spread. This paper updates various innovations on control of dengue vectors. Gene-based sterile insect technique using the RIDL technology for both Aedes aegypti & Ae albopictus control has now been actively researched and field trials are pursued to evaluate the effectiveness of the technology. The release of Wolbachia-infected Ae aegypti is another dengue control innovation. The infected mosquito cannot support development of dengue virus and has shorter life span. Other innovations include: auto-dissemination of insect control agents using ovitrap, autocidal adult and larva trap, outdoor residual spraying, insecticidal paint and biocontrol agent. In other innovation, outbreak prediction capability is enhanced by developing model based on environmental data and analysis utilising neural network.